The structure changes on a steels surface after pulsed plasma processing (International Journal of Mathematics and Physics, 2013)
The structure changes on steels surface, modified by plasma processing, are researched. The nano size structure, formed after plasma processing, is investigated by X-ray analysis and metallographic methods. Is shown, that phase consist of surface define by plasma parameters and the size of formed crystallites strongly influence on physical properties of materials